Introduced species and their effects on biodiversity conservation in Africa (2016)
Exotic/Introduced species has been spread all over the world either deliberately or accidentally and have no doubt contributed both positively and negatively to human existence over the years. So many of these introduced species became invasive in their introduced range. Ecologically and economically, the impacts of introduced/invasive species pose a threat, not only on our biodiversity, but also on human existence itself. It will be a double disaster if man does not recognize this disaster and harness its resources in order to curtail the menace. Control of alien species has been recommended by both theoretical and field conservationists. However, in order to be able to control invasive species effectively, prevention of any other introduction must be effected. Keeping potentially damaging invaders out is the most cost-effective way to deal with introduced species. Targeting common pathways by which invaders reach our shores can slow or stop their entry. As important as the need for control of Introduced/invasive species is, care must be taken on how and which method(s) of control is used at a particular time and in a particular situation for a particular species, so as to prevent any complication as much as possible. The paper therefore highlights few examples of introduced species in Africa, their impact, as well as ways of controlling them.